1979
DOI: 10.1007/bf01851331
|View full text |Cite
|
Sign up to set email alerts
|

Binding of copper to mucosal transferrin and inhibition of intestinal iron absorption in rats

Abstract: 1. The chromatographic elution patterns on Sepharose 6B of the supernatant from mucosal homogenates prepared 10 min after administration of copper into duodenal segments in vivo, indicate that copper is bound preferentially in the fraction of mucosal transferrin. 2. In iron deficiency the amount of 64Cu-copper taken up into the duodenal mucosa is more than two times higher and the amount bound to proteins of the supernatant is also increased to approximately the same degree whereas the amount transferred into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…These authors also showed, in duodenal loop experiments, that lack of DMT1 impaired copper absorption in iron-deficient (i.e., Belgrade) rats (as compared to normal littermate controls). DMT1 could thus, at least in part, mediate increased copper transport into duodenal enterocytes during iron deprivation, which would support the observation that copper content increased in the duodenal epithelium during ID (78, 248). Given these disparate results, further experimentation and documentation is required to establish a possible role of intestinal DMT1 in copper homeostasis during ID, and during physiological (and possibly pathological) conditions in other mammalian species (besides mice).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinesupporting
confidence: 74%
“…These authors also showed, in duodenal loop experiments, that lack of DMT1 impaired copper absorption in iron-deficient (i.e., Belgrade) rats (as compared to normal littermate controls). DMT1 could thus, at least in part, mediate increased copper transport into duodenal enterocytes during iron deprivation, which would support the observation that copper content increased in the duodenal epithelium during ID (78, 248). Given these disparate results, further experimentation and documentation is required to establish a possible role of intestinal DMT1 in copper homeostasis during ID, and during physiological (and possibly pathological) conditions in other mammalian species (besides mice).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinesupporting
confidence: 74%
“…Jiang et al (49) also used the DMT1-overexpression HEK293 cell model as well as a complementary ex vivo duodenal loop model to provide evidence that DMT1 transports copper specifically during iron deprivation. These observations suggest that DMT1 could, at least in part, mediate noted increases in copper content of the intestinal epithelium in rodent models of iron deficiency (22, 97). However, further experimentation is required before a consensus can be reached regarding a physiological role for DMT1 in copper homeostasis.…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 83%
“…HIF signaling in the intestine is of particular interest because copper was shown to be required for transactivation of gene expression by the HIF transcriptional complex (which contains a hypoxia-responsive HIFα subunit and a constitutively expressed HIFβ subunit) (24, 69). It may then be logically postulated that increased copper levels in enterocytes (22, 97), in the liver, and in the blood (17, 21) potentiate HIF activity, leading to transactivation of genes that participate in intestinal (and whole-body) iron homeostasis. Interestingly, the HIFα subunits are also stabilized by iron deprivation in vivo and in vitro (83).…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…The competition between iron and copper is typical: they share at least two membrane proteins, transferrin and metalotionein. Excessive copper bound to those protein may lead to iron deficiency (El Shobaki & Rummer, 1979).…”
Section: Mineral Utilization By Poultrymentioning
confidence: 99%